2019
DOI: 10.5614/j.math.fund.sci.2019.51.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Complex (PEC) of the Alginate-Chitosan Membrane for Immobilizing Urease

Abstract: PEC of the alginate-chitosan membrane as supporting material for immobilizing urease was produced. This study aimed to develop a supporting material for enzyme immobilization that has high stability, a fast response time and an easy and relatively inexpensive preparation procedure. An alginatechitosan PEC membrane was produced by reacting alginate hydrosol and chitosan (1:1 in mass) at pH 5.28, followed by mixing and drying at room temperature. The FTIR spectra, XRD patterns and SEM assay confirmed that algina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The crosslinked beads were filtered and stored at 4 °C for future use. The beads were lyophilized and surface morphology was observed using scanning electron microscopy on a SEM, Quanta FEG 250 machine [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The crosslinked beads were filtered and stored at 4 °C for future use. The beads were lyophilized and surface morphology was observed using scanning electron microscopy on a SEM, Quanta FEG 250 machine [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…ALG as a polyanion and CS as a polycation can create interactions between ALG carboxyl groups and CS amino groups. The combination of these polymers is characterized by better mechanical and thermal stability and higher adhesive properties than their constituent polymers [ 6 , 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Here, the morphology of the alginatechitosan membrane mixed was less homogeneous, it can be observed that the transparent membrane surface of the alginate-chitosan shows a fibrous structure with a rough morphology and irregular shape, which is a network of electrostatic interactions of alginate and chitosan. The likeness of its surface morphology has been described at previously work 6,9 .…”
Section: Preparation Of Transparent Pec Membranementioning
confidence: 99%
“…The membrane was prepared from hydrosols of chitosan and alginate, as described by Hermanto et al 6,9 . The scanning electron microscope (SEM) study was carried out on a transparent PEC membrane after being coated with gold palladium on SEM (Joel LV 5600 USA model) to evaluate the morphology and structure of membrane surface, as shown in Fig.…”
Section: Preparation Of Transparent Pec Membranementioning
confidence: 99%
See 1 more Smart Citation